1989
DOI: 10.1073/pnas.86.4.1421
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile hormone bisepoxide biosynthesis in vitro by the ring gland of Drosophila melanogaster: a putative juvenile hormone in the higher Diptera.

Abstract: The in vitro production of juvenile hormone (JH) was investigated by using isolated ring glands from third instar Drosophila melanogaster. A JH-like molecule is secreted that comigrates with a synthetic sample of methyl 6,7;10,11-bisepoxy-3,7,11-trimethyl-(2E)-dodecenoate (JHB3) during TLC, liquid chromatography, and GC analysis. Purified product from farnesoic acid-stimulated ring glands was analyzed by electron impact GC/MS and gave a mass spectrum identical to synthetic JHB3. Additional structure confirmati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
116
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(119 citation statements)
references
References 20 publications
2
116
0
1
Order By: Relevance
“…No clear orthologue to Cyp15a1 is identifiable in D. melanogaster (28). However, unlike in D. punctata, JH III bisepoxide (JHB 3 ) is thought to be the major JH produced in D. melanogaster (70). JHB 3 is synthesized by an alternate pathway possibly involving 2 epoxidation reactions catalyzed by a P450, converting farnesoic acid to JHB 3 (71).…”
Section: Discussionmentioning
confidence: 99%
“…No clear orthologue to Cyp15a1 is identifiable in D. melanogaster (28). However, unlike in D. punctata, JH III bisepoxide (JHB 3 ) is thought to be the major JH produced in D. melanogaster (70). JHB 3 is synthesized by an alternate pathway possibly involving 2 epoxidation reactions catalyzed by a P450, converting farnesoic acid to JHB 3 (71).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to JHB 3 , JH III and MF are also found as products in the CA in Phormia regina (Yin et al, 1995) and Neobellieria bullata (Bylemans et al, 1998). But in Lucilia cuprina (Lefevere et al, 1993), Drosophila melanogaster (Richard et al, 1989) and Calliphora vomitoria (Cusson et al, 1991) the production of JH III or MF is negligible. This is also true in P. terraenovae.…”
Section: Discussionmentioning
confidence: 98%
“…A combination of the radiochemical assay and various chromatographic analyses, such as TLC, high performance liquid chromatography and gas chromatography-mass spectrometry has demonstrated that the CA and ring glands in cyclorrhaphous flies predominantly biosynthesize JHB 3 (Yin, 1994). JHB 3 has been identified first in Drosophila melanogaster (Richard et al, 1989) and later in other cyclorrhaphous species (Yin and Stoffolano, 1997). In addition to JHB 3 , JH III and MF are also found as products in the CA in Phormia regina (Yin et al, 1995) and Neobellieria bullata (Bylemans et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…JH 0, I, II, and III have all been isolated from lepidopteran insects, whereas JH III, the presumed evolutionary precursor to the higher homologs, is found in all insects. JH bisepoxide (JHB3) has been identified as a product of the corpus allatum (CA) in higher Diptera including Drosophila melanogaster and Sarcophaga bullata (Richard et al, 1989;Bylemans et al, 1998). Nearly identical in structure to JH III, JHB3 is distinguished by an additional epoxide group spanning C6-C7.…”
Section: Jh and Jhas: Insecticidal Use Of Hormone Agonistsmentioning
confidence: 99%